Organizational culture, organizational learning and performance of firms - Ngugi, Peter Kiboi; Komen, Joyce; Korir, Michael (Eximia, 2021)
Organizational culture has been identified as an effective factor that determines how things get done in an organization. It is intangible, provides direction and aligns to the business vision and mission, helping decision making, prioritizing activities and defining accountability thus becoming the most important word in the business boardroom. Organizational learning is the process of creating, retaining, and transferring knowledge within an organization and an organization improves over time as it gains experience. From this experience, an organization is able to create knowledge. Organizational learning capability is important to develop other capabilities. A learning organization is the term given to an organization or a firm that facilitates the learning of its members and continuously transforms itself. A firm need to accumulate past experience and transform individual knowledge into organizational knowledge and then with the aid of continuous learning the firm should develop competence required to adopt to environmental changes. Organizational performance comprises the actual output of results of an organization as measured against its intended outputs. Listed commercial organizations at the stock exchange trade for profits and performance indicates level of profitability. Organizational learning as a dynamic capability helps organizations in coordinating internal and external information to sustain their knowledge management systems and gain competitive advantage. Cultural values then impact what might be expected actions moderating performance of these organizations. Despite the value of these interactions, in business, there are few empirical studies that have tested the underlying assumptions of the influence of culture on the dynamic capability organizational learning. The aim of this study was to determine the moderating effect of organizational culture on the relationship between dynamic capability organizational learning, on organizational performance in commercial organizations listed in Nairobi securities exchange. A cross sectional research design was adopted, where the target population of the sixty-seven listed companies was to be focused making it a census survey. Data was collected using a 5 Likert -scale questionnaire, data was analyzed using descriptive and inferential statistics using multiple linear regression. The study indicated that organizational learning capability had a statistically significant influence on organizational performance (_=0.348, p=.000). Organizational culture had a moderating effect on the relationship between organizational learning capability and performance (_R2=0.069, p=.000). It is therefore recommended that organizational learning while important in managerial activities had an inverse relationship with organizational performance but the results were not significant, while entrepreneurial culture should be enhanced.